Everyday Dilemmas and Challenges of a School Teacher - Yadav, Manisha; Aneja, Mansi (JOURNAL OF INDIAN EDUCATION, 2025)
It is often a popular perception to consider a school teacher’s job as unchallenging, monotonous and repetitive. The authors, using the framework of Berlak and Berlak (1981), found out that in the perceptions of teachers themselves, their job is extremely stressful, involves critical decision-making and resolution of dilemmas on a daily basis, and it is often a non-rewarding endeavour. The majority of teachers’ dilemmas centered on the issues of control mechanisms, curriculum transaction and societal concerns. The present study explores four research questions: (1) what are the daily dilemmas faced by the teachers while transacting curriculum, (2) what are the underlying reasons for the most stated dilemmas from the perspectives of teachers, (3) besides teaching the prescribed content, what are the expectations and responsibilities from the teachers, (4) how do teachers perceive their role as agents of change and transformation in a school? The sample of the study comprises 30 teachers from two government schools and two private schools teaching the middle grades. The data has been collected through semi-structured interviews and focus group discussions over a course of two months.